INNOVATION AND CREATIVITY SANGGABUANA BANDUNG UNIVERSITY IN PRINTING SUPERIOR HUMAN RESOURCES - Y. Ony Djogo (Pasundan International of Community Services Journal (PICS-J), 2020)
Competitive advantage is the ability of an organization to formulate a strategy that places it in a favorable position with respect to other organizations. It is not easy to make HR a source of competitive advantage for a company because it is related not only to ability and expertise, but also to personal factors such as values, perceptions, attitudes, personality and individual willingness to advance. Human resources are said to have a competitive advantage if they have unique skills and personalities that match the company personality where they work. Innovations and strategies for developing human resources in managing organizations are a solution to the economic business challenges.